Effect of Capital Structure and Growth Opportunity on Firm Value (Case Study on Manufacturing Companies on the Stock Exchange Indonesian Securities) - Burhanuddin Burhanuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
The calculation results obtained using the multiple linear regression analysis models show that capital structure and growth opportunity simultaneously have a positive and significant influence on firm value. This is supported by the F-counted value of 4,645 at the 0.011 significance level smaller than 0.05, which means that the F-count is greater than the F-table value of 4,645> 3,058. The capital structure is partially insignificant to the company. This is supported by the T-count value of 0.273 at a significance level of 0.785 greater than 0.05, which means that the T-count is smaller than the T-table value of 0.273 <1.976. The growth opportunity is partially negative and significant. This is supported by a T-count value of -3.033 at a significance level of 0.003, smaller than 0.05, which means the amount smaller than the T-table value is -3.033 <1.994.